2016
DOI: 10.1002/lio2.33
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy for non‐stone disorders: The current evidence

Abstract: ObjectiveReview the current literature on the use of sialendoscopy in the treatment of non‐stone disorders of the major salivary glands.Data SourcesEligible articles that reported on the use of sialendoscopy in the treatment of non‐stone disorders were identified using MEDLINE, Embase, and Google Scholar through May 2016. The search used key words sialendoscopy, salivary endoscopy, salivary scope, salivary duct stenosis, salivary duct stricture, Sjogren's disease, radioiodine sialadenitis, salivary duct obstru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 48 publications
2
20
0
2
Order By: Relevance
“…The vast majority of studies on outcomes after sialendoscopy show good results for the treatment of ductal stenoses with short‐term success rates of up to 93.8% 19,22,24 . In this study—as has been reported by others ( 22,25 )—about 20% of the glands treated by sialendoscopy needed a revision procedure over time. Few publications have reported any detailed analysis of the cause for recurrence 13,26 …”
Section: Discussionsupporting
confidence: 75%
“…The vast majority of studies on outcomes after sialendoscopy show good results for the treatment of ductal stenoses with short‐term success rates of up to 93.8% 19,22,24 . In this study—as has been reported by others ( 22,25 )—about 20% of the glands treated by sialendoscopy needed a revision procedure over time. Few publications have reported any detailed analysis of the cause for recurrence 13,26 …”
Section: Discussionsupporting
confidence: 75%
“…Both disorders may be complicated by bacterial infections [8]. While the therapeutic benefits of sialendoscopy have been demonstrated in many studies and reviews [911], the effects of sialadenitis and sialendoscopic intervention on patients’ health-related quality of life (HRQoL) have been investigated less often. Also, the costs related to the treatment of these patients and to sialendoscopy have not been comprehensively explored.…”
Section: Introductionmentioning
confidence: 99%
“…While evidence of symptom resolution following sialendoscopy in the treatment of nonstone disorders has been reported, prior studies have been largely retrospective and of smaller sample sizes. 14,19,[21][22][23] These retrospective analyses have demonstrated successful long-term complete or significant symptom resolution in 70% to 88% of patients following sialendoscopic procedures. 14,23 This prospective study echoes these findings to show that significant symptom reduction can be achieved in over half of patients with chronic idiopathic sialadenitis following treatment with sialendoscopy, although this patient population requires longitudinal follow-up due to high rates of symptom persistence and recurrence.…”
Section: Discussionmentioning
confidence: 99%